Assessment of historic stone arch bridge characterisation: experiments and numerical model. Issue 7 (2nd August 2018) - Mai, Khai Quang; Lee, Sung-Min; Lee, Kihak
Abstract : The importance of historic stone arch bridges in Korea is based on their very long period of use and their ability to change the landscape. The inherent variations in a bridge's constituent materials, its deterioration over time and other types of damage directly affect the structural response of these heritage structures. In order to characterise the structural components and behaviour of a masonry arch bridge in Korea, a series of full-scale experiments including dynamic measurements, non-destructive tests and advanced geomatics techniques were conducted. Three-dimensional (3D) models of Hongye-gyo Bridge were created using commercial finite-element (FE) software and various modifications were also made to enhance the computer model. Using experimental and numerical results obtained with advanced technologies, a rational definition of the material properties and structural geometry was simulated with a 3D FE model. It was found that, despite the complexity of masonry stone arch bridges, reasonable assumptions of material properties and the friction angle between the voussoir's interfaces enable a good prediction of a bridges' actual performance with a margin of 12%.